الحماية القانونية لإلستثمار األجنبي المباشر من المخاطر غير التجارية في الجزائر حسب المشرع الوطني - ايسان، داسي (جامعة الوادي University of El Oued, 2025)
تعتمد الدولة الجزائرية على إجراءات معينة لحماية الاقتصاد، بما في ذلك توفر ميزانية متوازنة ومنتج حديث وعالي الجودة. وذلك لأن الدولة الجزائرية ليست وكالة حكومية يمكنها ضمان استمرار تدفق الأموال إلى الاقتصاد. أجرت الدراسة تحليلاً شاملاً للإطار التنظيمي للاستثمار في الاقتصاد الجزائري، مع التركيز على المخاطر التجارية مثل المخاطر السياسية والاقتصادية والاجتماعية. كما بحثت دور اللوائح الدولية والإقليمية في معالجة هذه المخاطر، وخاصة تلك المتعلقة بالاتفاقيات الثنائية، وأهمية الحفاظ على بيئة استثمارية قوية وشفافة. وخلصت الدراسة إلى أن الجزائر تواجه تحديات كبيرة في إنشاء إطار تنظيمي قوي، مما يستلزم اتباع نهج شامل وفعال للاستثمار. The Algerian state relies on certain measures to protect the economy, including the availability of a balanced budget and a modern, high-quality product. This is because the Algerian state is not a government agency that can guarantee the continued flow of funds into the economy. The Algerian state is not a government agency that can guarantee the continued flow of funds into the economy. It is not a government agency that can guarantee the continued flow of funds into the economy. It is not a government agency that can guarantee the continued flow of funds into the economy. This ... The study conducted a comprehensive analysis of the regulatory framework for investment in the Algerian economy, focusing on trade risks such as political, economic, and social risks. It also examined the role of international and regional regulations in addressing these risks, particularly those related to bilateral agreements, and the importance of maintaining a robust and transparent investment environment. The study concluded that Algeria faces significant challenges in establishing a robust regulatory framework, which necessitates a comprehensive and effective approach to investment.
قانون أعمال
Keywords: الاستثمار الأجنبي المباشر والمخاطر غير التجارية.; Foreign‬Direct‬Investment; ‬Non-Commercial‬Risks